Protective Effect of Montelukast Which Is Cysteinyl-Leukotriene Receptor Antagonist on Gentamicin-Induced Nephrotoxicity and Oxidative Damage in Rat Kidney. (April 2013) - Otunctemur, Alper; Ozbek, Emin; Cekmen, Mustafa; Cakir, Suleyman Sami; Dursun, Murat; Polat, Emre Can; Somay, Adnan; Ozbay, Nurver
<x xml:space="preserve">Abstract</x> Nephrotoxicity is a major complication of gentamicin (GEN). We aimed to evaluate the potential protective effect of montelukast (MK) against GEN-induced nephrotoxicity in rats. Thirty-two rats were randomly divided into four groups, each consisting of eight animals as follows: (1) the rats were control; (2) intraperitoneally injected with GEN 14 consecutive days (100 mg/kg/day); (3) treated with GEN plus distilled water via nasogastric gavage for 14 days; and (4) treated with GEN plus MK (10 mg/kg/day) for 14 days. After 15 days, rats were killed and their kidneys were taken and blood analysis was performed. Twenty-four hours urine collections were obtained in standard metabolic cages a day before the rats were killed. Tubular necrosis and interstitial fibrosis scoring were determined histopathologically in a part of kidneys; nitric oxide (NO), malondialdehyde (MDA), and reduced glutathione (GSH) levels were determined in the other part of kidneys. Statistical analyses were made by the chi-square test and analysis of variance. Serum urea and creatinine levels were significantly higher in rats treated with GEN alone, than the rats in control and GEN + MK groups.The GSH levels in renal tissue of only GEN-treated rats were significantly lower than those in control group, and administration of MK to GEN-treated rats significantly increased the level of GSH. The group that was given GEN and MK had significantly lower MDA and NO levels in kidney cortex tissue than those that was given GEN alone. In rats treated with GEN + MK, despite the presence of mild tubular degeneration and tubular necrosis are less severe, and glomeruli maintained a better morphology when compared with GEN group. We can say that MK prevents kidney damage with antioxidant effect, independently of NO.